(untitled) (Research, Society and Development, 2022)
Objectives: To describe the perfusionist’s attributions and to highlight the skills and competencies developed during the training of nurses, which qualify them for the operationalization of Extracorporeal Circulation. Methodology: This is an integrative review study. Results: According to data from the Brazilian Society of Extracorporeal Circulation, there are 568 health professionals registered/working as perfusionists, 252 of whom are nurses, which corresponds to 44.4%. Conclusion: Specialization and professional activity as a perfusion nurse is a field little explored by nurses. In this way, it is proposed to explain and dialogue during the undergraduate course, as well as the exercise of reflection on the potential of professional performance, adding knowledge and knowledge in order to expand possibilities in the professional field. Holistic embracement and humanized care are attributions of the perfusionist nurse that distinguishes him from other professionals. The nurse in the role of perfusionist tests the machine, controls and checks supplies; the control of materials and expiration dates are checked in advance, days before the surgical procedures. The theme becomes relevant insofar as it can encourage the performance of similar studies, in order to corroborate, add and update the limited database on the subject addressed.